Pembelajaran Modifikasi Nutrasetikal Temu Mangga Menjadi Produk “Temapro” untuk Kesehatan Masyarakat - Miksusanti Miksusanti; Risfidian Mohadi; Aldes Lesbani; Nirwan Syarif; Neza Rahayu Palapa; Azhar Kholiq; Syafrina Lamin (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
This community service program aims to develop nutraceutical-based health products from temu mangga (Curcuma mangga Val.van Zip) and probiotics, called "TEMAPRO". Research and socialization were conducted in Pulau Semambu Village, South Sumatra, targeting village mothers who have limited knowledge about the benefits of herbs and probiotics. Temu mangga, which is traditionally consumed as a salad and herbal medicine, contains various active compounds that have the potential as antioxidants and anti-cancer. Combined with the probiotic Lactobacillus rhamnosus, this product is expected to support digestive health and increase body immunity. Implementation methods include education, training in making temu mangga extract, mixing with probiotics, and product packaging techniques. The results of the activities showed an increase in community understanding and skills in processing local materials into health products with economic value. It is hoped that "TEMAPRO" will not only improve the quality of public health, but also open up business opportunities in the village through local nutraceutical products.